The productivity of trypanotolerant livestock in West and Central Africa - Trail, J.C.M.; Wissocq, Y.J. (1982)
Reports on the productivity of trypanotolerant breeds in 18 West and Central African countries. Traits examined included reproductive performance, cow and calf viability, milk production, growth and body weight of cattle within a village or ranch management system and under four degrees of trypanosomiasis risk levels. The results were used to build productivity indices, and compared productivity of these breeds with crosses of zebu and humpless cattle. A coordinated research and project network is recommended.